Effect of Heat-moisture Treatment on the Structure and Gel Properties of Hydroxypropyl Starch - SUN Qing-jie; XU Zi-hui; SUN Qi; JI Na; QIN Yang (Liang you shipin ke-ji, 2024)
Hydrogels prepared by hydroxypropyl starch have better tensile properties than ordinary starch, but their mechanical properties are relatively poor. In this paper, effect of the heat-moisture treatment on the physical, chemical and the gel properties of hydroxypropyl starch was studied. Compared with the control group, the thermal stability of starch has been improved and the maintenance value decreased from 12.55 J/g to 6.58 J/g. The XRD analysis showed that the crystallicity of the strength from 30.4% to 19.6%. The double helix in strength was first destroyed by heat-moisture treatment. The peak viscosity of hydroxypropyl starch first rose to about 5 000 cp and then dropped to about 3 000 cp. The TPA and the rheological analysis showed that the hardness of the starch increased after the heat treatment of 223.51 g to 463.50 g and the storage elastic module increased, indicating that wet heat treatment improved the mechanical properties of the starch.